The application of osteopathic treatments to pediatric sports injuries - Bolin, D. J. (Pediatric Clinics of North America, 2010)
The application of manual techniques to pediatric athletic injuries has been considered alternative medicine. There are many injuries that are associated with loss of normal motion. Altered biomechanics can be readily identified and treated using manual methods. These include articular or thrust techniques, muscle energy, strain-counterstrain, and myofascial treatments, among others. Although there are few high-quality studies available, most available literature reports effectiveness of manual techniques in combination with therapeutic exercise for common pediatric motion restrictions.